2002
DOI: 10.1159/000068020
|View full text |Cite
|
Sign up to set email alerts
|

Initial Lithium and Valproate Combination Therapy in Acute Mania

Abstract: Early onset of treatment efficacy is especially important for severe mania syndromes. Lithium has usually a delayed onset of response, which is disadvantageous for inpatient treatment of severe mania. Valproate is effective in treating acute mania and has sedative properties. It has, however, a response rate of approximately only two thirds. Therefore, the initial combination of valproate and lithium was evaluated in a prospective case series of 12 patients, and a retrospective analysis was carried out for 5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Available evidence suggests use of combination of mood stabilizers in cases of patients with treatment-resistant mania. [ 52 53 54 ] Use of clozapine in treatment-refractory manic cases is well established,[ 55 56 57 58 59 60 ] yet it lacks the regulatory approval for use in any phase of BD. [ 61 ] In the present study too, clozapine was found to be more often used in those with manic residual symptoms when compared with other two groups with residual symptoms, possibly suggesting these to be treatment-refractory cases.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests use of combination of mood stabilizers in cases of patients with treatment-resistant mania. [ 52 53 54 ] Use of clozapine in treatment-refractory manic cases is well established,[ 55 56 57 58 59 60 ] yet it lacks the regulatory approval for use in any phase of BD. [ 61 ] In the present study too, clozapine was found to be more often used in those with manic residual symptoms when compared with other two groups with residual symptoms, possibly suggesting these to be treatment-refractory cases.…”
Section: Discussionmentioning
confidence: 99%
“…Second, bipolar mania is characterized by a broad set of symptoms and not all manic individuals exhibit motor hyperactivity (Einat, 2007b). Third, while acute lithium treatment has been demonstrated to attenuate amphetamine-induced hyperactivity in rodents (Berggren et al, 1981), the specificity of this effect is debatable and the therapeutic effect of lithium in bipolar patients may not appear for weeks (Reischies et al, 2002). …”
Section: Animal Models Of Bipolar Disordermentioning
confidence: 99%
“…The most commonly used pharmacological interventions for bipolar disorder are antidepressants, lithium, the anticonvulsants~e.g., carbamazepine and lamotrigine!, and the novel antipsychotics~e.g., olanzapine; Grunze, 2005;McIntyre, 2002!. Most of these medications have an impact on sleep. Typically they are either sedating Ghaemi, Manwani, Katzow, Ko, & Goodwin, 2001;Makela, Miller, & Cutlip, 2003;McIntyre, 2002;Reischies, Hartikainen, & Berghofer, 2002;Sorge, Pollmaecher, & Lancel, 2004! and0or alter sleep architecture~Bazil, 2003Gann, Riemann, Hohagen, Muller, & Berger, 1994;Geurkink, Sheth, Gidal, & Hermann, 2000;Kupfer, Wyatt, Greenspan, Scott, & Snyder, 1970;Sharpley, Vassallo, & Cowen, 2000;Sharpley, Walsh, & Cowen, 1996!.…”
Section: Treatmentmentioning
confidence: 99%